The power of legitimacy: local cooperation and the effectiveness of peace operations - Whalan, J (2010)
This thesis investigates how peace operations work. It contributes to the larger study of peace operation effectiveness by analysing the processes through which these institutions influence local actors in postconflict societies. Looking beyond traditional concerns with mandates and resources, it aims to understand how a peace operation seeks to achieve its goals, focusing on why local populations might cooperate with or obstruct its activities. The thesis draws on theories of social power, compliance and legitimation to answer four central questions: what power do peace operations have to achieve their objectives? From where do peace operations derive power? How do local perceptions of an operation enable or constrain its effectiveness? How are peace operations legitimised at the local level, and with what effect? It begins by critically reviewing the academic literature, arguing that existing approaches are unable to account for important dimensions of peace operation effectiveness because they neglect the local setting in which operations pursue their goals, and the extent to which the achievement of those goals requires local cooperation. It then develops an analytical framework to examine the processes of coercion, inducement and legitimacy through which peace operations seek to shape the decisions and actions of local actors. This power-legitimacy framework is applied to study the effectiveness of the United Nations Transitional Authority in Cambodia (UNTAC) and the Regional Assistance Mission in Solomon Islands (RAMSI). By comparing variation in local cooperation between and within these cases, the thesis shows that the way a peace operation is locally perceived is an important but often overlooked determinant of its effectiveness. In particular, when local actors perceive a peace operation to be legitimate, they are more likely to behave in ways that assist the operation to achieve its goals. The thesis concludes by discussing the implications of this finding for the future study and practice of peace operations.